Pengaruh Strategi Pemasaran, Kemampuan dan Pengetahuan Wirausaha terhadap Keberhasilan Usaha Mikro Kecil Menengah (UMKM) di Kota Mojokerto - Putri Ayu Lestari; Imam Baidlowi; M. Syamsul Hidayat (Pusat Riset dan Inovasi Nasional, 2024)
Development in general depends on an economy based on broad community participation, which can be seen from the Micro, Small and Medium Enterprises (MSME) sector which is one of the most common types of business. The small and medium enterprise (MSME) sector is an important part of the country's economy. Micro, Small and Medium Enterprises (MSMEs) play a strategic role in national economic development because they really help economic growth and obtain workers, as well as distributing development results. However, success in developing a business so that it can help economic development is determined by various factors such as effective marketing strategies, mental and physical readiness of entrepreneurs, as well as in-depth knowledge of markets and products. This research aims to determine the influence of marketing strategy, entrepreneurial ability and entrepreneurial knowledge on business success among MSMEs in the city of Mojokerto. This type of research is quantitative research. The population in this study was all MSME actors in the culinary sector in Mojokerto City, totaling 2,527 MSMEs and the sample of respondents was 96 MSMEs using purposive sampling techniques. Respondent data was collected using a questionnaire. The data analysis method for this research uses descriptive statistical analysis using classical assumption testing and multiple linear regression, the overall analysis of which is calculated using the Statistical Program For Social Science (SPSS) version 25. The results of this research show that marketing strategy has a positive and significant effect on business success, entrepreneurial ability has no at all significant effect on business success, and entrepreneurial knowledge has a positive and significant effect on business success. Meanwhile, the most influential variables are marketing strategy variables and entrepreneurial knowledge. Based on simultaneous or joint testing, it was found that marketing strategy, entrepreneurial ability and entrepreneurial knowledge had a positive and significant effect.